The Puerto Rico Journal of Public Health and Tropical Medicine (1925-1949): Coverage of Tropical Sprue - Preston, Alan (Puerto Rico Health Sciences Journal, 2023)
Our current understanding of tropical sprue is that it is a malabsorption syndrome that responds to treatment with folic acid and a broad spectra antibiotic. This realization came only after countless years of research by legions of investigators. Twenty-seven individual studies on various aspects of tropical sprue were published in the Puerto Rico Journal of Public Health and Tropical Medicine from 1925 to 1949. This article summarizes significant findings, presented chronologically, and speculates on the direction of future investigations into tropical sprue.